Den Jerusalemitiske tempelkult iflg. Jesaja 1, 10-17 - Gottlieb, Hans (Religionsvidenskabeligt Tidsskrift, 1984)
1,10-17 is the oldest text which provides a more subtle insight into the cult of the Yahweh Temple in Jerusalem. It is therefore an appropriate source for describing this cult. As an introduction, the sacrificial terminology of th text is analysed, specifically zæbah, ‘ôlâ, minhâ and qetoræt. Concerning qetoræt it is concluded that the word does not denote the smoke of sacrifice, but the incense, which simultaneously symbolizes and veils the presence of the god during the ceremony. The text is thereafter confronted with the modern-day interpretation of the cult. It is demonstrated that a series of aspects, which research has found in the antique conception of the cult, i.e. sacrifice as engendering fellowship, as a gift to the god, as food for the god, are more or less clearly present in the text. The text is supplemented with Mi 6,7, which mentions sacrifice of the first born, sinoffering and human sacrifice. Concerning human sacrifice, the idea that it should not be considered a legitimate part of the official Yahweh Cult during times of distress is rejected. In conclusion, the description of various aspects of the antique conception of sacrifice in the research literature is returned to. It is claimed that the text as a whole can be considered a rejection of the conception of sacrifice as a religious duty. The rejection is due to the fact that Isaiah and his contemporaries were agreed that purity is a prerequisite of correct sacrifice, but were in disagreement as to the nature of purity. Purity for Isaiah is an ethical conception, i.e. to do what is right. Isaiah places emphasis upon the social side of ethics in the text here.